Investigating of the role of cybercrime and e-brand trust on purchase interest of e-commerce platforms - Mohammad Fadil Imran; Hendra Gunawa (International Journal of Data and Network Science)
In this digital era, the use of the Internet in business transactions through e-commerce platforms has created many conveniences, the development of Internet technology has given rise to crimes called cyber crime or crimes through the Internet network. The purpose of this study is to investigate the relationship between cybercrime and purchase intention on e-commerce platforms, and the relationship between e-brand trust and purchase intention on e-commerce platforms. This research method is a quantitative method to analyze the relationship between variables, research data was obtained by distributing online questionnaires through social media platforms, and questionnaires containing statement items were designed using a Likert scale of 1 to 5. The respondents of this study were 535 consumers who had shopped online on e-commerce platforms determined by the simple random sampling method. Data analysis used the PLS Partial least squares SEM (PLS-SEM) technique. In the study, the outer model which is called the measurement model has a meaning between indicators connected by other variables. The measurement model of convergent validity, discriminant, and reliability was used. The standard loading factor value in the concurrent validity test must be > 0.7 or greater than the established criteria. The same applies to the discriminant validity test, which uses a larger value for the loading factor. The construct reliability test uses Cronbach's alpha and the composite reliability value. The hypothesis testing uses partial least square (PLS) which is the inner model test result, namely the R-square output, path coefficient, or t-statistic. The convincing t-statistic result > 1.96 is that Ha is accepted and Ho is rejected. If the probability number (p-value) <0.005 is included, then Ha is accepted. If the p-value is <0.05 (or 5%), the t-statistic is > 1.96, and the beta coefficient is positive, then Ha can also be accepted. The results of the analysis show that cybercrime has a positive effect on consumer purchasing intentions on e-commerce platforms and e-brand trust hurts consumer purchasing intentions on e-commerce platforms.